Validação de método espectrométrico para quantificação de um derivado de N-Acilhidrazona - Araújo, Gisele Jacinto de (2023)
The synthesis of new acylhydrazonic derivatives has presented a great scientific interest, due to their potential analgesic, anti-inflammatory and antimicrobial actions. In this sense, when it comes to newly synthesized molecules, the development and validation of quantification methods is of utmost importance, since they do not have analytical methods reported in official compendia. The objective of this work was to develop and validate an analytical method for the quantification of an N-acylhydrazonic derivative (JR-19) using UV-VIS molecular absorption spectrometry. A Shimadzu UV-1280 spectrophotometer was used for spectrometric measurements, DMSO was used as solvent for preparing stock and working solutions. Initially, spectral scanning was carried out in the UV-Vis region to determine the maximum radiation absorption region, choosing the wavelength of 311 nm. Then, the stability of the JR-19 solutions was evaluated in short (8 hours) and medium (14 days) terms, varying storage conditions (temperature and photodegradation). The results indicated that the solutions stabilize after 2 hours of preparation and that the best storage procedure is at room temperature (25 ºC) and that they do not undergo photodegradation, therefore not needing to be protected from light. Ensuring the stability of the solutions, the proposed method was validated following the parameters recommended by DOQ-CGCRE-008, being harmonized with ANVISA's RDC 166 of 2017, based on the figures of merit: Linearity, selectivity, accuracy, precision, detection limit, quantification limit and robustness. The method was considered linear in the range of 2 to 17 µg mL-1. The limits of detection and quantification were 0.5831 and 1.7669 µg mL-1, respectively, ensuring the sensitivity of the method. The method was considered accurate with coefficients of variation lower than 5%. The accuracy was evaluated from the recovery test and the values averaged 97,17%. For robustness, two factorial designs were performed for each brand of DMSO, so that the coefficients of variation presented were less than 5% for the responses obtained by the different brands, being corroborated by the Pareto diagram and graph of surface and response, considering the method robust. Therefore, it can be concluded that the developed method is within acceptable standards in terms of the recommended quality parameters.